2023
DOI: 10.1111/nph.18770
|View full text |Cite
|
Sign up to set email alerts
|

Integrating plant physiology into simulation of fire behavior and effects

Abstract: Summary Wildfires are a global crisis, but current fire models fail to capture vegetation response to changing climate. With drought and elevated temperature increasing the importance of vegetation dynamics to fire behavior, and the advent of next generation models capable of capturing increasingly complex physical processes, we provide a renewed focus on representation of woody vegetation in fire models. Currently, the most advanced representations of fire behavior and biophysical fire effects are found in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 192 publications
0
8
0
Order By: Relevance
“…First, they reveal management-relevant axes of flammability trait variation for the two study species that are strongly influenced by tissue moisture (and by extension, drought tolerance traits). As climate and fire regimes change, there has been a push to incorporate these types of physiological response traits into global-scale fire risk and behaviour models (Dickman et al, 2023). Boving et al (2023) then demonstrate how their "ignitabilitycombustibility" proxy is linearly correlated to leaf water potentials.…”
mentioning
confidence: 99%
“…First, they reveal management-relevant axes of flammability trait variation for the two study species that are strongly influenced by tissue moisture (and by extension, drought tolerance traits). As climate and fire regimes change, there has been a push to incorporate these types of physiological response traits into global-scale fire risk and behaviour models (Dickman et al, 2023). Boving et al (2023) then demonstrate how their "ignitabilitycombustibility" proxy is linearly correlated to leaf water potentials.…”
mentioning
confidence: 99%
“…Recent studies have shown the major role of physiological traits (vulnerability to cavitation, hydraulic segmentation and transpiration regulation) on both leaf and canopy fuel moisture content (Ruffault et al ., 2023), but more research is needed to scale up predictions from the leaf or canopy level to the stand or landscape levels. It is also necessary to achieve a better integration between short‐term physiological LFMC models (Balaguer‐Romano et al ., 2022; Ruffault et al ., 2023) and microclimatic variation driven by the fire‐plume so that this effect can be added to dynamical fire behaviour modelling (Dickman et al ., 2023).…”
Section: Linkage Between Hydraulics‐related Plant Traits and Wildfire...mentioning
confidence: 99%
“…Progress in pyro‐ecophysiology requires communication between plant physiologists and fire scientists who have, until recently, focused largely on questions within their fields rather than linkages between them. For example, fire behaviour models rarely incorporate plant physiology beyond generalizations of live fuels into broad functional groups, while relationships between plant water and various aspects of fire ecology, including fire behaviour and the ecological effects of fire, are largely unresolved (Dickman et al, 2023; Jolly & Johnson, 2018). Additionally, these two fields often use different metrics to assess tissue hydration and its effects on drought, fire impacts and vegetation characteristics.…”
Section: Introductionmentioning
confidence: 99%